Developing Learning Design Employing Problem Based Learning with Mind Mapping of Excretory System Material to Develop Critical and Creative Thinking Ability for Junior High School Students - Yulianti, Eva Lia; Alimah, Siti (Journal of Biology Education, 2021)
This present study aimed at producing a feasible learning design employing problem-based learning with mind mapping model to develop the ability of critical and creative thinking for Junior high school students in the excretory system material. This research belongs to Research and Development following ADDIE research model without including the implementation stage. The stages which were adopted in this research stopped on the development stage. The products of the developed learning design are lesson plan, learning module, student worksheet, and test instrument. The data collection technique of this research was validation by seven validators involving expert lecturers and science teachers to examine the validity and quality of the learning design. The validation analysis result showed that the learning design is categorized into â€œvery validâ€ criteria in each scoring aspect. Based on that analysis, the learning design is valid and is able to be tested in the learning activity. However, the validators gave comment and suggestion which were used to improve the products. The test instrument was tested for students and its result was analyzed to figure out the validity, reliability, level of difficulty, and discriminating power of the test items. Based on the items analysis, six question items are classified as valid, reliable, having a moderate level of difficulty, and having a good discriminating power. The final result of this research produces a development product of leaning design that is feasible to be brought into testing.